2009
DOI: 10.1038/tpj.2009.25
|View full text |Cite
|
Sign up to set email alerts
|

APOE gene polymorphisms and response to statin therapy

Abstract: Published studies investigating the role of APOE gene on lipid response (total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides) to statin treatment have reported inconsistent results. A meta-analysis was conducted to estimate the lipid response to statin treatment among APOE genetic variants (e2 carriers, e3e3 homozygotes and e4 carriers). Twenty-four studies were included in the meta-analyses. The pooled mean reduction (Dm) in TC fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…However, a future meta-analysis of multiple studies clearly has a role in offering an analysis with the potential for higher power. 28,29 Future collaborative studies may allow the pooling of data, providing more power to detect significant associations. Furthermore, consortia performing gene-candidate or genome-wide association studies will be able to replicate the validity of the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, a future meta-analysis of multiple studies clearly has a role in offering an analysis with the potential for higher power. 28,29 Future collaborative studies may allow the pooling of data, providing more power to detect significant associations. Furthermore, consortia performing gene-candidate or genome-wide association studies will be able to replicate the validity of the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a study by Zintzaras et al, 21 the results were not significant regarding the relationship between the genetic variants of APOE and plasma lipid levels. However, in a study by Smart et al, 22 variants of genes of lipoprotein lipase, namely CETP-Taq1B, APO E, APOA5, APOA4 and APOC3, were associated with plasma levels of healthy pediatric populations.…”
Section: (1) Association Of Genetic Variation Of Abcb1mentioning
confidence: 77%
“…In fact, Sedano et al [8] point out that most studies that have found an association between the e4 allele and most aggressive forms of MS were carried out in Northern Europe [5,15,16,17,18], and most studies that failed to find an association were carried out in Southern Europe [7,8,9,11]. Environmental factors like diet might act on the ApoE gene and explain these differences, as has been proposed in publications about the response to treatment with statins [27]. …”
Section: Discussionmentioning
confidence: 99%